Makbet Giuseppe Verdiego wobec romantycznej recepcji - Borkowska-Rychlewska, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
Romantic approach to William Shakespeare’s dramatic works, as well as the notions and questions so vital for the consciousness of the epoch concerning the capacity and function of destiny, unrecognizability of existence, interference of supernatural powers in the world that can be grasped with human mind and common sense, are all intriguingly transparent in Giuseppe Verdi’s Macbeth. The Italian composer, who knew the Romantic reception of Shakespeare’s dramatic plays well (e.g. the Italian translations of the lectures given by August W. Schlegel), embarked upon the issue of the ambiguity of the scene with the witches that appear to Macbeth, posed a question on the cognitive value in the dreamy apparition (in the brilliantly constructed Lady Macbeth’s sleepwalking scene), and, finally, emphasized the aspect of hybridity of the world that inseparably combines the grandeur and the grotesque (the point highlighted in Victor Hugo’s considerations on Shakespeare). The two versions of the operatic Macbeth — the one produced in Florence in 1847, the other, 1865 revised version produced for Paris — relate well with the long sequence of changeable conventions in the nineteenth century theatre, taking into consideration its requirements (the need for a spectacular character of staging, the introduction of multiple Ake a Romantic implant in the operetta world of farcical braggadocio dominant on the Parisian stage at the time of the Second Empire, testifies to the enormous influence of the Romantic reception of Shakespeare exerted at the time and defining for a considerable period of time the concept of adaptation of the works of the Stradford master to meet the needs of the operatic stage.